INVESTIGATION ON ELASTIC CONTACT DYNAMIC STRESS OF A DEEP-GROOVE BALL BEARING BASED ON EXPLICIT DYNAMICS - TU WenBing; LUO Ya; WANG ChaoBing; ZHANG Long; CHEN QiPing (Jixie qiangdu)
Rolling element bearing is an important kind of machine element widely used in mechanical industry,and its internal stress condition has great influence on its service life. Considering the characteristic of elastic nonlinear contact in rolling element bearing,taking deep-groove ball bearing 6304 as investigation object,a flexible finite element dynamic model for contact nonlinear dynamic problem of a deep-groove ball bearing was established. Based on explicit dynamic finite element method,a nonlinear contact dynamic simulation was made and the kinematics characteristic of deep-groove ball bearing and contact stress of inner ring,outer ring and rolling element were obtained. The regularity of dynamic stress varying in motion process was studied.The results show that the present explicit dynamics finite element method is very efficient and reliable in solving complicated rolling element bearing dynamics stress,and it will become a useful means for the further work on rolling element bearing carrying capacity and service life.